Practitioner Courage and Ethical Health Care Environments - Oakley, Justin (The Hastings Center report, 2015)
In this issue of the Hastings Center Report, Ann Hamric, John Arras, and Margaret Mohrmann highlight how contemporary accounts of the virtue of courage in health care often gloss over deeper problems in the underlying health care systems themselves. They express particular concerns about the appropriateness and personal costs of exhortations to health professionals to take courageous action in circumstances where this is “required only because of unethical institutional structures” (p. 39). They offer valuable points that are not adequately recognized in discussions of courage as a professional virtue in health care practice. The call for more judicious appeals to health professionals to exercise courage in health care practice should clearly be heeded. A sole reliance on practitioner courage for exposing unethical workplace practices would be misguided. Nevertheless, there is still a legitimate place for encouraging health professionals to develop and act on courage.